Critical infrastructure and strategic resilience of the state - Stefan Czmur (Przegląd Komunikacyjny)
Abstract: Recently, the COVID-19 pandemic and the events related to Russia's aggression against Ukraine, as well as the general increase in tension in international relations, have put the global, regional and national security systems of individual countries to a severe test. Experiences from these events provide many conclusions that should be used in the process of adapting security systems to the new and constantly changing political-military, economic, social and natural environment. These experiences have highlighted the importance of the strategic resilience of the state, as well as of alliances. This was reflected in both national and allied normative documents. In the North Atlantic Alliance, the Resilience Committee was established as the highest advisory body for strategic resilience and preparing the society to function in times of crisis and war. In several countries, intensive work is underway to develop a state resilience strategy linked to a national security strategy. Unlike the latter, state resilience strategies are designed to limit the risk of disruption to the most basic functions of the state and society to an acceptable level and ensure that they can be restored in a reasonable time and at a reasonable price.